The effect of gender on negotiation behaviour - Dobrijević, Gordana (The European Journal of Applied Economics, 2014)
As men and women have different roles in society, their negotiating styles and behaviours are also different. The success of men and women in negotiations depends largely on the type of negotiation (integrative or distributive) and gender stereotypes prevailing in society. There is a general opinion that women are more cooperative, while men are more aggressive and competitive in negotiations. Our findings from the Serbian setting show a somewhat different picture: women do not use more cooperative strategies and tactics than men. Although men focus on winning, they also focus on problem solving; while women focus on conflict avoidance, and, to a certain extent, on mutual relationship. Women are also more sensitive to their counterpart’s age and gender. But, they are also less sincere in negotiations and focus on their own interests, rather than taking care of their own as well as other party’s interests. A major theoretical implication of this research is that the observed differences in the behaviour of female negotiators reflect the pressure to be successful in a male-dominated society where gender stereotypes are quite prominent.